2001
DOI: 10.2337/diabetes.50.3.558
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vagal Cooling on the Counterregulatory Response to Hypoglycemia Induced by a Low Dose of Insulin in the Conscious Dog

Abstract: We previously demonstrated, using a nerve-cooling technique, that the vagus nerves are not essential for the counterregulatory response to hypoglycemia caused by high levels of insulin. Because high insulin levels per se augment the central nervous system response to hypoglycemia, the question arises whether afferent nerve fibers traveling along the vagus nerves would play a role in the defense of hypoglycemia in the presence of a more moderate insulin level. To address this issue, we studied two groups of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 33 publications
0
14
1
Order By: Relevance
“…[41][42][43][44] In contrast, the activation of glucagon secretion by insulin-induced hypoglycemia was not inhibited by inactivating the hepatic vagal nerve, suggesting that this sensor did not participate in the induction of counterregulation. [45][46][47] However, more recent data showed that celiac-superior mesenteric ganglionectomy, but not vagotomy, suppressed the response to insulin-induced hypoglycemia, suggesting that the hepatoportal sensor may indeed participate in triggering glucagon secretion. 48,49 In the central nervous system, sites of glucose detection for the control of counter-regulation are present in the hypothalamus and different brainstem nuclei.…”
Section: Counter-regulationmentioning
confidence: 99%
“…[41][42][43][44] In contrast, the activation of glucagon secretion by insulin-induced hypoglycemia was not inhibited by inactivating the hepatic vagal nerve, suggesting that this sensor did not participate in the induction of counterregulation. [45][46][47] However, more recent data showed that celiac-superior mesenteric ganglionectomy, but not vagotomy, suppressed the response to insulin-induced hypoglycemia, suggesting that the hepatoportal sensor may indeed participate in triggering glucagon secretion. 48,49 In the central nervous system, sites of glucose detection for the control of counter-regulation are present in the hypothalamus and different brainstem nuclei.…”
Section: Counter-regulationmentioning
confidence: 99%
“…Stainless steel cooling coils, with Silastic extension tubing attached, were placed around the vagus nerves in the neck in all dogs, as described previously (1,10). The effectiveness of the cooling-induced blockade of parasympathetic signaling was verified by measuring the heart rate (which is under vagal control).…”
Section: Methodsmentioning
confidence: 99%
“…Free fatty acids (FFAs), cortisol, lactate, and glycerol were measured as previously described (4,17).…”
Section: Methodsmentioning
confidence: 99%